2006
DOI: 10.1111/j.1600-0528.2006.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental risk attitudes and caries‐related behaviours among immigrant and western native children in Oslo

Abstract: The results suggest that immigrant groups in western societies require different information packages, modified strategies for forming oral hygiene habits and attitudes related to dental care of children, and encouragement to exercise discipline on factors known to be risks for oral health. These strategies must recognize that immigrants and western natives attach different levels of importance to oral health and dental parameters. It should be paid extra attention to some caries high-risk subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
119
1
17

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(149 citation statements)
references
References 21 publications
12
119
1
17
Order By: Relevance
“…Other parent-related factors associated with a high caries experience at 15 years of age were 'father not satisfied with his social situation', 'mother who was a single parent when the child was 1 year old' and 'the mother feeling that she was alone with the responsibility for the child in the family'. This is in accordance with Skeie et al [2006], who found that there was a relationship between a father who accompanied the child to the clinical examination and low caries experience in the child. This indicates that the family situation is important and that responsibility shared by both parents could have a positive impact on good oral health.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Other parent-related factors associated with a high caries experience at 15 years of age were 'father not satisfied with his social situation', 'mother who was a single parent when the child was 1 year old' and 'the mother feeling that she was alone with the responsibility for the child in the family'. This is in accordance with Skeie et al [2006], who found that there was a relationship between a father who accompanied the child to the clinical examination and low caries experience in the child. This indicates that the family situation is important and that responsibility shared by both parents could have a positive impact on good oral health.…”
Section: Discussionsupporting
confidence: 76%
“…However, their family is still an important mediator of socialisation and the development of health-related behaviours [Åstrøm, 1998]. Children's dental health habits are associated with the dental health behaviour of their parents and their role persists in a significant manner during childhood [Mattila et al, 2000[Mattila et al, , 2005a, as well as during adolescence [Åstrøm and Jakobsen, 1996].In recent decades, Sweden has gradually become more multicultural as a result of immigration, which has been reported to have consequences for the dental health of children and adolescents [Grindefjord et al, 1996;Wendt et al, 1999;Stecksén-Blicks et al, 2004;Julihn et al, 2006;Skeie et al, 2006]. According to Burt [2005], 'we should broaden our view of risk to include social determinants of health and population health'.…”
mentioning
confidence: 99%
“…This was also true when caries frequency was compared. Our result was in accordance with previous studies from Sweden (Bankel, Eriksson et al 2006, Jacobsson, Koch et al 2011, Stecksén-Blicks, Hasslöf et al 2014) and other Scandinavian countries (Skeie, Riordan et al 2006, Christensen, Twetman et al 2010. The number of children with CL/P and immigrant background (n = 9) was too small and therefore suboptimal for looking at differences in caries prevalence/frequency and birthplace.…”
Section: Dental Caries Risksupporting
confidence: 81%
“…The reason for this seems to be a high consumption of sugary products and poor oral hygiene within these risk groups (Skeie, Riordan et al 2006, Stecksén-Blicks, Hasslöf et al 2014.…”
Section: Etiology To Dental Cariesmentioning
confidence: 99%
“…There are numerous risk indicators associated with caries development in preschool children; both socioeconomic status, feeding habits and early colonization of caries bacteria has been linked to caries development (6). In Norway, documentation of association between caries prevalence in preschool children and risk indicators is limited to few studies on selected populations (7,8). Previous caries experience has been considered the best predictor of future caries development in children (9), but this predictor is not useful for children having their first carious lesion.…”
Section: Introductionmentioning
confidence: 99%